A Short Review on Polymer Nanocomposites for Enameled Wires: Possibilities and Perspectives - Danikas, M.; Morsalin, S. (Engineering, Technology & Applied Science Research, 2019)
Polymer nanocomposites constitute a new generation of insulating materials, capable of offering better electrical, thermal and mechanical properties. Past research indicated that such materials may replace conventional polymers for a variety of industrial high voltage applications. In the present paper, polymer nanocomposites are investigated regarding the insulation of enameled wires. Possible nanocomposite candidates are discussed.